Analysis of the influence of socio-cultural factors on the development of youth entrepreneurship - V. Alieva; V. Parakhina; O. Boris (Вестник Северо-Кавказского федерального университета)
This article analyses the influence of socio-cultural factors on the entrepreneurial activity of the younger generation. In recent years, there has been a noticeable decline in the development of small and medium-sized businesses in the Russian Federation. During the global economic crisis, which affected our country as well, there is a growing demand for a new generation of young entrepreneurs capable of playing more active role in the economy, business and society. The development of youth business should contribute not only to the training of qualified staff, but also to the fast-track transition of the country to the innovative path in the context of digital economy formation and progression. The article aims to investigate the impact of education, values and family background on entrepreneurs. The detailed review of the relevant literature and empirical research proved that socio-cultural factors are very important for raising new entrepreneurs, creation of new enterprises and, as a result, ensuring the growth of this segment of economy.